Bacterial shifts during in-situ mineralization bio-treatment to non-ferrous metal(loid) tailings. (December 2019) - Liu, Jian-li; Yao, Jun; Duran, Robert; Mihucz, Victor G.; Hudson-Edwards, Karen A.
Abstract: Nonferrous mine tailings have caused serious problems of co-contamination with metal(loid)s. It is still a global challenge to cost-effectively manage and mitigate the effect of the mining wastes. We conducted an in-situ bio-treatment of non-ferrous metal(loid) tailings using a microbial consortium of sulfate reducing bacteria (SRB). During the bio-treatment, the transformation of metal(loid)s (such as Cu, Fe, Mn, Pb, Sb, and Zn) into oxidizable and residual fractions in the subsurface tended to be higher than that observed in the surface. As well the mineral compositions changed becoming more complex, indicating that the sulfur reducing process of bio-treatment shaped the bio-transformation of metal(loid)s. The added SRB genera, especially Desulfotomaculum genus, colonized the tailings suggesting the coalescence of SRB consortia with indigenous communities of tailings. Such observation provides new insights for understanding the functional microbial community coalescence applied to bio-treatment. PICRUSt analysis revealed presence of genes involved in sulfate reduction, both assimilatory and dissimilatory. The potential for the utilization of both inorganic and organic sulfur compounds as S source, as well as the presence of sulfite oxidation genes indicated that SRB play an important role in the transformation of metal(loid)s. We advocate that the management of microorganisms involved in S-cycle is of paramount importance for the in situ bio-treatment of tailings, which provide new insights for the implementation of bio-treatments for mitigating the effect of tailings. Graphical abstract: Image 1 Highlights: The in-situ bio-treatment of nonferrous metal(loid) tailings was effective. The treatment contribute to the transformation of metal(loid)s. The added consortium coalesce with indigenous communities and colonize the tailings. Bacterial communities were enhanced during bio-treatment. PICRUSt predicted genes for using inorganic and organic sulfur compounds as S sources.